Option values in the market for periurban developable land - Jean Cavailhés; Mohamed Hilal; Pierre Wavresky (European Regional Science Association (ERSA), 2010)
We study the developable land market in French periurban and rural areas under urban influence. Theoretical aspects and empirical results are derived from urban economics to analyse the main determinants of the price of developable land: distance from the urban centres, population, inhabitantsí income, etc. We focus especially on option values that come from irreversibility of development of farmland into residential plots, with uncertainly and inflow of information from the market. The classical option value, due to temporal price volatility (ìprice riskî), is introduced into an econometric model. The novel contribution of the paper is to introduce also uncertainly regarding the spatial volatility of the demographic evolution in a spatial buffer around each transaction (ìpopulation riskî), which generates a second option value. We use three individual data sets that describe the market of developable land: a very complete database available for the North department3 (31551 observations from 1989 to 2003); comparisons are made with two others database available for the CÙte-díOr department (3303 observations) and the Toulouse region (10293 observations). We use an econometric random effects model: random variables capture the effects of unobservable or omitted variables characterising each commune (level 2 of the French Local Administrative Units) or urban areas (commuting or shopping zones). Price uncertainly is introduced from the classical approach of a Brownian movement with drift (Dixit et Pindyck, 1994; cf. discussion in Cunningham, 2006): the conversion decision is made from the observed variability of the residential land price during the preceding months. We model in the same way the ìpopulation riskî: it depends on population evolution in neighbouring communes between the population censuses of 1982 and 1999; the price of waiting for more information from migrations when population is fluctuating turns into an option value capitalized into the price of developable land. The findings show, on the one hand, the decreasing slope of the price of developable plots according to both distance from urban centres and distance from the centre of each commune, the role of population and of its evolution, etc. On the other hand, significant option values appear. They are linked, first, to the ìprice riskî. In the Nord department, when the standard deviation of the price of developable plots during the six previous quarters rises by a standard deviation, the land price increase by 7.4% during the downward period of the real estate cycle (1989-1997) and in 15.3% during the upward period (1998-2002). Option values also are linked to the ìpopulation riskî: prices significantly rise with population volatility. In the Nord department, during the upward period, an increase by one standard deviation of the standard deviation of 1982-1999 population variation entails an increase by 6% of the developable land price.
Keywords: 330